Regret minimization based joint econometric model of mode choice and departure time: a case study of university students in Toronto, Canada. Issue 2 (29th November 2019) - Anowar, Sabreena; Faghih-Imani, Ahmadreza; Miller, Eric J.; Eluru, Naveen
ABSTRACT: With the objective of enhancing our understanding of student travel patterns, we examine their mode and departure time choice for discretionary trip purposes. In our study, we hypothesize that students are likely to consider these joint choices or interconnected decisions in a sequence (mode first, departure time second and departure time first, mode second), even if the time difference between these decisions is infinitesimally small. A latent segmentation approach is proposed that allows for the incorporation of choice sequences simultaneously. Within this framework, mode and departure time decisions are examined using random utility and random regret decision framework. This is the first application of such a joint sequential system using a regret-based decision rule. Our results indicate that students are more likely to choose their departure time first and then mode. A policy exercise is also conducted to demonstrate the applicability of the proposed model system.